A Brief Screening Tool to Assess the Risk of Contracting HIV Infection Among Active Injection Drug Users. Issue 3 (May 2015) - Smith, Dawn K.; Pan, Yi; Rose, Charles E.; Pals, Sherri L.; Mehta, Shruti H.; Kirk, Gregory D.; Herbst, Jeffrey H.
<x xml:space="preserve">Abstract</x> Objective: To incorporate preexposure prophylaxis and other biomedical or intensive behavioral interventions into the care of injection drug users (IDUs), health care providers need validated, rapid, risk screening tools for identifying persons at highest risk of incident HIV infection. Methods: To develop and validate a brief screening tool for assessing the risk of contracting HIV (ARCH), we included behavioral and HIV test data from 1904 initially HIV-uninfected men and women enrolled and followed in the AIDS Linked to the Intravenous Experience prospective cohort study between 1988 and 2008. Using logistic regression analyses with generalized estimating equations, we identified significant predictors of incident HIV infection, then rescaled and summed their regression coefficients to create a risk score. Results: The final logistic regression model included age, engagement in a methadone maintenance program, and a composite injection risk score obtained by counting the number of the following 5 behaviors reported during the past 6 months: injection of heroin, injection of cocaine, sharing a cooker, sharing needles, or visiting a shooting gallery. The area under the receiver operating characteristic curve was 0.720; possible scores on the index ranged from 0 to 100 and a score 46 or greater had a sensitivity of 86.2% and a specificity of 42.5%, appropriate for a screening tool. Discussion: We developed an easy to administer 7-question screening tool with a cutoff that is predictive of incident HIV infection in a large prospective cohort of IDUs in Baltimore. The ARCH-IDUs screening tool can be used to prioritize persons who are injecting illicit drugs for consideration of preexposure prophylaxis and other intensive HIV prevention efforts.